Processual antecedents of perceived channel conflict in franchising - Weaven, Scott K.; Grace, Debra A.; Frazer, Lorelle; Giddings, Jeffery (Journal of Business Economics and Management, 2014)
In this study, we develop and examine the network of relationships explaining perceived conflict in franchise relationships from a franchisee perspective. Our research contributes to the current knowledge of asymmetric exchange relationships through demonstrating the importance of a franchisee's expectations confirmation, relational trust and relationship satisfaction in franchisee assessments of network conflict. The goal of this paper is to empirically examine (1) the relationship between franchisee perceptions of information quality (information dissemination and information search) and the confirmation of franchisee performance expectations, (2) franchisee characterizations of their relationships with their franchisors in terms of relational sentiments such as trust and relational satisfaction, communication and conflict management, (3) the relationship between franchisee satisfaction and perceived conflict, and (4) the moderating effect of franchisee experience on the relationship between franchisee satisfaction and franchisee perceptions of conflict. Empirical results, utilizing a sample of 345 franchisees in Australia, present strong evidence for the support of nine of the ten hypotheses drawn from the conceptual model. Specifically, data reveal that in an effort to cultivate a network of cooperative and satisfied franchisees, franchisors should adopt strategies that promote the timely dissemination of relevant and meaningful pre- and post-entry information, open communication exchange, transparent conflict management systems and personalized support in accommodating individual franchisee needs.